Multi-organ point-of-care ultrasound for COVID-19 (PoCUS4COVID): international expert consensus - Arif Hussain; Gabriele Via; Lawrence Melniker; Alberto Goffi; Guido Tavazzi; Luca Neri; Tomas Villen; Richard Hoppmann; Francesco Mojoli; Vicki Noble; Laurent Zieleskiewicz; Pablo Blanco; et al. (Critical Care, 2020)
Abstract COVID-19 has caused great devastation in the past year. Multi-organ point-of-care ultrasound (PoCUS) including lung ultrasound (LUS) and focused cardiac ultrasound (FoCUS) as a clinical adjunct has played a significant role in triaging, diagnosis and medical management of COVID-19 patients. The expert panel from 27 countries and 6 continents with considerable experience of direct application of PoCUS on COVID-19 patients presents evidence-based consensus using GRADE methodology for the quality of evidence and an expedited, modified-Delphi process for the strength of expert consensus. The use of ultrasound is suggested in many clinical situations related to respiratory, cardiovascular and thromboembolic aspects of COVID-19, comparing well with other imaging modalities. The limitations due to insufficient data are highlighted as opportunities for future research.